WAYS TO INCREASE STUDENTS’ INTEREST IN LEARNING FOREIGN LANGUAGES USING ARTIFICIAL INTELLIGENCE. (Лучшие интеллектуальные исследования, 2025)
Abstract: Language learning, a cornerstone of global communication and cultural understanding, can often be a challenging and even daunting endeavor. Traditional methods, while effective, may not always capture and sustain the interest of all learners. The emergence of Artificial Intelligence (AI) has revolutionized the educational landscape, offering innovative and engaging approaches to language acquisition. This study explores how AI can be effectively utilized to motivate students, fostering a more dynamic, personalized, and rewarding language learning experience.